Size‐Related Electrochemical Performance in Active Carbon Nanostructures: A MOFs‐Derived Carbons Case Study. Issue 20 (21st August 2019) - Gadipelli, Srinivas; Li, Zhuangnan; Lu, Yue; Li, Juntao; Guo, Jian; Skipper, Neal T.; Shearing, Paul R.; Brett, Dan J. L.
Abstract: Metal–organic framework–derived carbon nanostructures have generated significant interest in electrochemical capacitors and oxygen/hydrogen catalysis reactions. However, they appear to show considerably varied structural properties, and thus exhibit complex electrochemical–activity relationships. Herein, a series of carbon polyhedrons of different sizes, between 50 nm and µm, are synthesized from zeolitic imidazolate frameworks, ZIF‐8 (ZIF‐derived carbon polyhedrons, ZDCPs) and their activity is studied for capacitance and the oxygen reduction reaction (ORR). Interestingly, a well‐correlated performance relationship with respect to the particle size of ZDCPs is evidenced. Here, the identical structural features, such as specific surface area (SSA), microporosity, and its distribution, nitrogen doping, and graphitization are all strictly maintained in the ZDCPs, thus allowing identification of the effect of particle size on electrochemical performance. Supercapacitors show a capacity enhancement of 50 F g −1 when the ZDCPs size is reduced from micrometers to ≤200 nm. The carbonization further shows a considerable effect on rate capacitance—ZDCPs of increased particle size lead to drastically reduced charge transportability and thus inhibit their performance for both the charge storage and the ORR. Guidelines for the capacitance variation with respect to the particle size and SSA in such carbon nanostructures from literature are presented. Abstract : Carbon‐based nanostructures are indispensable for supercapacitors, fuel cells, and batteries. Advancement in this area requires critical understanding of the form and function. Here, a well‐correlated relationship is demonstrated for the performance of supercapacitors and the oxygen reduction reaction with respect to particle size of metal–rganic frameworks–derived carbon. Surface area, pore‐size distribution, nitrogen doping, and graphitization are all maintained identical.